Soil stabilisation by water repellency under no-till management for soils with contrasting mineralogy and carbon quality - Behrends Kraemer, Filipe; Hallett, Paul D.; Morras, Hector; Garibaldi, Lucas Alejandro; Cosentino, Diego Julian; Duval, Matías; Galantini, Juan (Elsevier, 2019)
No-till soil management is common around the globe, but the impacts on soil structural quality varies depending on cropping practice and inherent soil properties. This study explored water repellency as a driver of soil stabilization, as affected by soil mineralogy, granulometry and organic carbon quality in three Mollisols and one Vertisol under no-till management and with different levels of cropping intensity. The studied soils were located along a west-east textural gradient in the northern part of the Pampean region of Argentina. Cropping intensity treatments evaluated in each one of the soils were: Poor Agricultural Practices (PAP) close to a monoculture, Good Agricultural Practices (GAP) involving a diverse crop rotation and more targeted inputs, and the soil in the surrounding natural environment (NE) as a reference. NE had the greatest aggregate stability (MWD) of all cropping intensities, with GAP being more stable than PAP for Mollisols and PAP being greater than GAP for the Vertisol. This trend matched the Repellency Index (Rindex), with greater Rin dex associated with greater MWD,including the difference between the Mollisols and Vertisol. However, the persistence Of water repellency,measured by the Water Drop Penetration Time (WDPT) test followed the trend NE GAP PAP regardless of soil type. The increases in Rindex and MWD were related to higher intensification as measured by the Crop Sequence Index, and decreased with greater soybean occurrence in the sequence. Both WI)PT and Rin dex were closely related to aggregate stability, particularly for Mollisols. These results highlight the importance of considering the inherent soil characteristics texture and mineralogy to understand aggregate stabilization mediated by water repellency. Good correlations between soil water repellency, organic carbon fractions and aggregate stability were found. Under no-till, crop rotations can be altered to increase soil stability by inducing greater water repellency in the soils. The findings suggest that water repellency is a major property influencing soil structure stabilization, thus providing a useful quality indicator.